2018
DOI: 10.1186/s12891-018-2000-3
|View full text |Cite
|
Sign up to set email alerts
|

Walking balance is mediated by muscle strength and bone mineral density in postmenopausal women: an observational study

Abstract: BackgroundDepletion of ovarian hormone in postmenopausal women has been associated with changes in the locomotor apparatus that may compromise walking function including muscle atrophy/weakness, weight gain, and bone demineralization. Therefore, handgrip strength (HGS), bone mineral density (BMD) and body composition [percentage body fat mass (%BFM), fat mass (FM), Fat-free mass (FFM) and body mass index (BMI)], may significantly vary and predict WB in postmenopausal women. Consequently, the study sought to 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 45 publications
0
8
0
1
Order By: Relevance
“…On the other hand, it has been demonstrated that there is a connection between walking balance and strength [80] and that sarcopenia influences walking balance [81]. A study with older adults with mild to moderate frailty improved their CRF but at a modest level [82].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that there is a connection between walking balance and strength [80] and that sarcopenia influences walking balance [81]. A study with older adults with mild to moderate frailty improved their CRF but at a modest level [82].…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of this study is that the BMD of the weight-bearing bones (BMDtoes) were significantly higher than the BMD of the non-weight-bearing bones (BMDthumbs). Weight-bearing activities which result in limb loading, such as walking, running, and close-chain kinetic movements [51][52][53], could provide a very potent osteogenic stimulus in PLWH, and is, therefore, bone protective. Consequently, weight-bearing activities could have beneficial effects on bone health in PLWH and explain why a previous study found that physical activity level is a major determinant of bone mass in postmenopausal women [54].…”
Section: Discussionmentioning
confidence: 99%
“…An active lifestyle should increase lean muscle mass [53] and boost physical activity which recruits the skeletal muscles and increases the loading traction on the bones thereby increasing shear strain that activates osteoblastic activities [66] in the presence of putative mediators such as nitric oxide, prostaglandins E (PGE) and (PGI) I, sclerostin, Insulin-like growth factor (IGF's), Transforming growth factor beta (TGFβ), Receptor Activator of Nuclear Factor-kappa B-Ligand (RANK-L), and osteoprotegerin (OPG). Shear stress generated with physical exercises, involving skeletal muscle contraction, induces the production of nitric oxide [67].…”
Section: Discussionmentioning
confidence: 99%
“…Além disso, fatores fisiológicos contribuem no metabolismo de recuperação do tecido musculoesquelético. A redução sérica de hormônios ovarianos pode impactar na recuperação de massa muscular, devido a sua ação no sistema musculoesquelético, interferindo na força e área da fibra muscular [20,21] e isso possui relação direta com a idade reprodutiva na vida de uma mulher. Talvez, mulheres no período menacme possam apresentar uma boa recuperação funcional por uma boa resposta musculoesquelética, o que podemos hipotetizar pelo resultado satisfatório do presente estudo.…”
Section: Discussionunclassified